2022
DOI: 10.1038/s41586-021-04269-6
|View full text |Cite|
|
Sign up to set email alerts
|

Mutation bias reflects natural selection in Arabidopsis thaliana

Abstract: Since the first half of the twentieth century, evolutionary theory has been dominated by the idea that mutations occur randomly with respect to their consequences1. Here we test this assumption with large surveys of de novo mutations in the plant Arabidopsis thaliana. In contrast to expectations, we find that mutations occur less often in functionally constrained regions of the genome—mutation frequency is reduced by half inside gene bodies and by two-thirds in essential genes. With independent genomic mutatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
426
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(471 citation statements)
references
References 89 publications
41
426
1
3
Order By: Relevance
“…We know germline mutation rates have been associated with other genomic features such as histone markers, transcription rate, and replication timing ( Chen et al 2017 ; Supek and Lehner 2019 ). Indeed, our model makes a prediction that mutation rate will be higher in genes, which is in contrast to a recent empirical study in Arabidopsis thaliana that found a lower mutation rate in coding sequence ( Monroe et al 2022 ). Their predictive model of mutation differs from ours in that it depends strongly on empirically estimated epigenetic factors that are not represented in our model.…”
Section: Resultscontrasting
confidence: 91%
“…We know germline mutation rates have been associated with other genomic features such as histone markers, transcription rate, and replication timing ( Chen et al 2017 ; Supek and Lehner 2019 ). Indeed, our model makes a prediction that mutation rate will be higher in genes, which is in contrast to a recent empirical study in Arabidopsis thaliana that found a lower mutation rate in coding sequence ( Monroe et al 2022 ). Their predictive model of mutation differs from ours in that it depends strongly on empirically estimated epigenetic factors that are not represented in our model.…”
Section: Resultscontrasting
confidence: 91%
“…The C➔T transitions that dominate the numt mutation spectrum are a hallmark of the abundant 5-methylcytosine (5mC) modifications at CpG and CHG sites in plant nuclear genomes (Vanyushin and Ashapkin 2011; Weng, et al 2019; Naish, et al 2021; Monroe, et al 2022). We found that 88 of the 235 C➔T observed SNVs occur at CpG sites, and an additional 87 occur at CHG sites.…”
Section: Resultsmentioning
confidence: 99%
“…2, Sup Fig 10). Before doing so, we masked all annotated genes and unmethylated (potential regulatory) regions under the assumption that intergenic sequences would be less likely to be constrained by selection (Lynch et al 2016; Monroe et al 2022). The divergence dating confirmed that cenhaps on seven chromosomes fall into two haplogroups with divergence times ranging from ∼450-130 mya.…”
Section: Resultsmentioning
confidence: 99%